2003
DOI: 10.1103/physrevb.67.144414
|View full text |Cite
|
Sign up to set email alerts
|

Doping effects on the phase separation in perovskiteLa0.67xBixCa<

Abstract: Effects of Bi, Cr, and Fe doping on phase separation of La 0.67 Ca 0.33 MnO 3 have been experimentally studied. As proved by the electron-spin resonance and neutron-diffraction studies, partial replacement of La by Bi causes the simultaneous occurrence of ferromagnetic ͑FM͒ phase and charge-ordered antiferromagnetic phase. As a consequence, two subsequent magnetic transitions at ϳ120 K and ϳ230 K are resulted. A strong coupling between the coexisted phases is assumed, which is responsible for the insensitivity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
23
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 41 publications
3
23
0
Order By: Relevance
“…Following this trend of work, more specific studies were focused on one of the main contributions to the physical properties of manganites. This is change in the crystallographic structure while maintaining a fixed doping level [6]. Several authors completed a great number of different cationic substitutions, which are briefly summarized in the phase diagram proposed by Hwang et al [7].…”
Section: Introductionmentioning
confidence: 99%
“…Following this trend of work, more specific studies were focused on one of the main contributions to the physical properties of manganites. This is change in the crystallographic structure while maintaining a fixed doping level [6]. Several authors completed a great number of different cationic substitutions, which are briefly summarized in the phase diagram proposed by Hwang et al [7].…”
Section: Introductionmentioning
confidence: 99%
“…The electron spin resonance (ESR), magnetization and neutron diffraction studies on La 0.67−x Bi x Ca 0.33 MnO 3 (x ≤ 0.20) reveal that the partial replacement of La by Bi develops the charge ordered AFM phase. 15 A large magnetic entropy change 20 and 087105-2 R. Ade and R. Singh AIP Advances 5, 087105 (2015) state switching behavior 21 have been also reported in Bi doped La-manganites. The evolution different properties with Bi doping can be due to the effect of 6 s loan pair of Bi 3+ ions.…”
Section: Introductionmentioning
confidence: 92%
“…The decrease in the unit-cell volume for these samples compared to La 0.67 Ca 0. 33 13,15,18 From the refinement the estimated atomic positions for the samples are listed in Table I. Microstructure of the samples Fig.…”
Section: A Structure and Morphology Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Zhang et al and it has been found that T CO and antiferromagnetic (AFM) ordering temperature T N occurring below T CO decrease with increasing Gd-doping level [14]. Despite several investigations relating to the doping on A site in Bi 1−x Ca x MnO 3 [15][16][17][18][19], the physical feature of CO, the interplay between the different magnetic phases and the nature of the resulting meta-magnetic phase is still unclear. Further, the nature of the phase separation (PS) [20] that plays a crucial role in determining the magnetic landscape of manganites is also only vaguely understood.…”
mentioning
confidence: 99%